The Influence of Flipped Classroom Pedagogy on Academic Achievement of Students at Higher Secondary Level: Usages of Social Network Sites as a Key Mediator - Wajid Mahnaz; Gulzar; Salma Bibi; Safeer Ullah (Social Science Review Archives, 2025)
The landscape of education has evolved significantly in recent years, driven by advancements in technology and innovative pedagogical approaches. Among these, the flipped classroom pedagogy has gained substantial attention for its potential to transform traditional teaching methods. The study aimed at to investigate “The Influence of Flipped Classroom Pedagogy on Academic Achievement of Students at Higher Secondary Level: Usages of Social Network Sites as a Key Mediator”. The objectives of the study were; 1) To explore the relationship between Flipped Classroom Pedagogy and Academic Achievement. 2) To examine the relationship between Flipped Classroom Pedagogy and the Usage of Social Network Sites (SNS). 3) To analyze the mediating role of the Usage of Social Network Sites (SNS) in the relationship between Flipped Classroom Pedagogy and Academic Achievement. Survey-based research method was employed for this study. Surveys were designed to collect quantitative data from students at the higher secondary level. A quantitative research design was adopted for this study. The total population for this study consisted of higher secondary school students in District Attock. There were 12 higher secondary schools for boys and 10 higher secondary schools for girls. The total number of male students was 9,024, while the total number of female students was 8,855. The sample for this study comprised 470 students enrolled in higher secondary schools in District Attock. A simple random sampling technique was employed to select the participants. Self developed questionnaires were used as research tools. Coefficient correlation was used for exploring the relationship between two different variables. The strong positive correlation (r = 0.848, p < 0.001) between Flipped Classroom Pedagogy and Academic Achievement suggests that flipped classroom practices significantly enhance academic performance. Hence, it is recommended to integrate flipped classroom approaches into the curriculum to improve students' academic outcomes, with a focus on active learning strategies and interactive activities.